Menelaah Tabiat Industri Televisi Rating Sudah Jadi Tauhid - Khusairi, Abdullah (AL MUNIR : Jurnal Komunikasi dan Penyiaran Islam, 2012)
Rating program is the average viewer to program expressed as a percentage of the group sample or total potential. The rating point program is based on the smallest unit of time one minute. Rating required for television stations to measure the success of an event and is closely related to the success of advertisers rating to "monotheism" is inevitable, to mention the focus of all current television program objectives. Recognized or not, in fact, any new impressions, emulated by other broadcasters. Finally booming and people accept there was a critical and agrees.